Modeling the tropical fish community related to land uses and environmental determinants - N. Takarina; O. Chuan; M. Afifudin; L. Tristan; I. Arif; A. Adiwibowo (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Coastal ecosystems worldwide have been threatened by changing land use and environmental determinants. These conditions have impacted important marine resources, including fish diversity. Southeast Asia, one region experiencing massive land use change, still has limited information on how land use and disturbed coastal ecosystems impact fish diversity. This information is urgently needed as fish is one of the most important food resources here. This study aims to assess and compare the environment and tropical fish community between disturbed and intact sites, represented by coasts dominated by settlements and coasts dominated by mangrove forests in West Java, Indonesia.METHODS: Fish sampling was carried out at two sites: Jakarta as the disturbed site and Subang as the intact site; water quality was also measured at these sites. Land uses at the sites were interpreted using satellite imagery. Fish diversity was determined using the Shannon–Wiener index, rarefaction curve, and Lorenz graph. Principal component analysis, analysis of variance, and the x2-test were used to determine environmental factors that affected the fish community at both sites. Akaike’s information criterion was assigned to model the relationship between environmental factors and the fish community.FINDINGS: Coasts characterized by anthropogenic disturbances and the absence of mangrove cover have a lower potential of hydrogen (pH) and reduced fish diversity by up to 53.91%. The intact site had higher fish diversity and made a greater contribution to conservation by providing habitats for fish species with the least concern and vulnerability statuses, according to the International Union for Conservation of Nature Red List. From the AIC model, the decreasing water pH (AICc = 27.28) was the main determinant that reduces fish diversity at disturbed sites compared to dissolved oxygen (Akaike’s information criterion = 28.13) and salinity (Akaike’s information criterion = 29.95).CONCLUSION: The coastal fish community was affected by differences in environmental factors, land uses, and mangrove cover driven by anthropogenic influences. The AIC model proved capable of assessing the effects of environmental factors on coastal fish communities. This study modeled environmental factors that should be managed and prioritized to restore and conserve the fish community along tropical coasts.